(untitled) (Revista Electrónica REDINE, 2021)
This review is related to the past, present and future of the “Gaceta Técnica” journal (ISSN: 2477-9539), a biannual, arbitrate and indexed scientific publication of the Civil Engineering Faculty, Universidad Centroccidental Lisandro Alvarado, Barquisimeto, Venezuela. Directed to professionals, researchers and academics in the area of ​​civil engineering in all its branches, architecture, urban planning, as educators who work in the aforementioned programs. It constitutes an academic space for the dissemination original scientific works, of an interdisciplinary and multidisciplinary nature. It started to be printed in 2000, and is currently online through the OJS publication platform with the address https://revistas2.uclave.org/index.php/gt. Gaceta Técnica maintaining quality standards, registered in portals, directories and databases such as: DOAJ, Revencyt, Redalyc, Latindex catalog v.2, Redib, Dialnet, Periódica and Scipedia.